Library logo competition entires (Raton, New Mexico, 2007)
Competition sponsored by the library, Friends of the library paid the prize.
logo competition submission forms and drawings from the applicants for the new library logo
Master list item #55
File location is in the Raton File Cabinet drawer 3
Keywords: Poe, Stacey -- Raton, New Mexico; Arthur Johnson Memorial Library -- Raton, New Mexico; Library Logo competition -- Raton, New Mexico; McQueary, Brad -- Raton, New Mexico; Donnelly, Rebecca -- Raton, New Mexico